BIOLOGY AND HISTORY OF CULTURE OF POMEGRANATE (PUNICA GRANATUM L.). Pomegranate GROWING COUNTRIES AROUND THE WORLD - M.Bobomurodov; M. Xolmuminova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the plant pomegranate (punica granatum). In addition, information is provided on the history, origin, biological characteristics of pomegranate (punica granatum), as well as species, in which regions they grow.